Thermal discomfort with cold extremities in relation to age, gender, and body mass index in a random sample of a Swiss urban population - Orgül Selim; Flammer Josef; Schötzau Andreas; Fontana Gasio Paola; Mozaffarieh Maneli; Kräuchi Kurt (BMC, 2010)
Abstract Background The aim of this epidemiological study was to investigate the relationship of thermal discomfort with cold extremities (TDCE) to age, gender, and body mass index (BMI) in a Swiss urban population. Methods In a random population sample of Basel city, 2,800 subjects aged 20-40 years were asked to complete a questionnaire evaluating the extent of cold extremities. Values of cold extremities were based on questionnaire-derived scores. The correlation of age, gender, and BMI to TDCE was analyzed using multiple regression analysis. Results A total of 1,001 women (72.3% response rate) and 809 men (60% response rate) returned a completed questionnaire. Statistical analyses revealed the following findings: Younger subjects suffered more intensely from cold extremities than the elderly, and women suffered more than men (particularly younger women). Slimmer subjects suffered significantly more often from cold extremities than subjects with higher BMIs. Conclusions Thermal discomfort with cold extremities (a relevant symptom of primary vascular dysregulation) occurs at highest intensity in younger, slimmer women and at lowest intensity in elderly, stouter men.